Atomic Configuration of Point Defect Clusters in Ion-Irradiated Silicon Carbide. Issue 1 (December 2017) - Lin, Y.; Chen, L.; Hsieh, C.; Chang, M.; Fung, K.; Hu, A.; Lo, S.; Chen, F.; Kai, J.
Abstract Silicon Carbide (SiC) is a promising cladding material for accident-tolerant fuel in light water reactors due to its excellent resistance to chemical attacks at high temperatures, which can prevent severe accident-induced environmental disasters. Although it has been known for decades that radiation-induced swelling at low temperatures is driven by the formation of black spot defects with sizes smaller than 2 nm in irradiated SiC, the structure of these defect clusters and the mechanism of lattice expansion have not been clarified and remain as one of the most important scientific issues in nuclear materials research. Here we report the atomic configuration of defect clusters using Cs-corrected transmission electron microscopy and molecular dynamics to determine the mechanism of these defects to radiation swelling. This study also provides compelling evidence that irradiation-induced point defect clusters are vacancy-rich clusters and lattice expansion results from the homogenous distribution of unrecovered interstitials in the material.